U.S.-China trade war and competitive advantage of Vietnam - Dhar B.K. (2023)
China has been losing international competitiveness in labor-intensive industries due to various factors, including the trade war with the United States and globalization. Vietnam, however, has rapidly expanded its labor-intensive exports. The paper proposes to explore the future of labor-intensive industries in Vietnam due to the U.S.-China trade war. The paper examines export performance data from United Nation Comtrade for 10 specific labor-intensive industries that serve the U.S. market between 2000 and 2020 to assess the possibility of Vietnam overtaking China's position as the world's largest manufacturer. Using situation analysis, the paper compares the competitive advantage of Vietnam in labor-intensive industries due to the U.S.-China trade war. The paper found that China's competitiveness was negatively impacted for the final two periods, while Vietnam's competitive advantage increased.